До походження та інтерпретації пам’яток волинцевського етапу культури літописних сіверян - Сухобоков, О.В. (Археологія, 1999)
Розглядаються питання походження та сучасної інтерпретації волинцевських пам'яток (кінець VII — середина VIII ст. н. е.), які, на думку автора, репрезентують ранні етапи історичного розвитку слов'ян Дніпровського Лівобережжя — сіверян «Повісті минулих літ». Речь идет о проблемах славянских памятников Левобережной Украины последней трети I тыс. н. э., среди которых наиболее дискуссионными являются древности волынцевского типа. Автор предлагает свое видение истоков этих памятников, вопросов их генетических связей, их места в культурно-стратиграфической колонке предгосударственных памятников Днепровского Левобережья, оставленных славянами северянского союза племен на раннем этапе их исторического развития.
Находясь на позициях автохтонизма, автор критически анализирует сформулированную В. В. Седовым гипотезу о происхождении волынцевских памятников из именьковской культуры Среднего Поволжья, носители которой якобы на рубеже VII и VIII вв. переселились в Среднее Поднепровье. Наряду с этим в статье не отрицается возможность микромиграций праболгарских племен из степей Северного Причерноморья, равно как и дунайских славян на территорию левобережноднепровской лесостепи. На счет этих мигрантов относится своеобразие волынцевских древностей, а их специфические черты объясняются влиянием инокультурного импульса на раннем этапе волынцевско-роменской культуры, представляющей летописных северян. The paper focuses on the problems of Slavic sites on the Left-bank Ukraine dated from the last third of the first millennium AD. The antiquities of the Volyntsevo type are the widest debated topic. The author proposes his own vision of the antiquities: their origin, generic relations and status in the cultural/stratigraphical list of those sites of the pre-state period within the Left-bank Dnieper Region that are attributable as the Slavic sites of the Siveriany Union of tribes at the early stage of their historical development.
Stating the autochthon position on the issue, the author critically analyses the hypothesis (developed by V.V.Sedov) on that the Volontsevo type had originated from the Imenkovo Culture of the Middle Volga Region; according to the hypothesis, the tribes of the Imenkovo Culture resettled to the Middle Dnieper Region at the end of the seventh/beginning of the eighth centuries. The author does not disclaim the possibility of the micro-migrations of the proto-Bulgarian tribes from the steppes of the Northern Black Sea Region and the Danubian Slavs to the territory of the Dnieper River Forest-Steppe Zone. The migrations are responsible for the peculiarities of the Volyntsevo antiquities, and their specific features are attributed to the external impacts at the early stage of the Volyntsevo-Romny Culture, which represents the Annalistic Siveriany.